Efficacy of florfenicol for the treatment of infections by Pasteurella multocida and Mannheimia haemolitica in alpacas (Vicugna pacos) - Ferrante, Marcos (2019)
The aim of the study was to evaluate the effect of florfenicol treatment at a dose of 20 mg/kg via i.m. in the treatment of infections caused by Pasteurela multocida and Mannheimia haemolitica in alpacas. The efficacy rate was determined according to the minimum inhibitory concentration (MIC) of the infecting bacterium. For this, a Monte Carlo simulation of pharmacokinetic parameters for 10 000 events and pharmacokinetic/pharmacodynamic analysis (PK/PD) was performed. The estimated efficacy rates for P. multocida were 99, 20 and 1% and according to the MICs of strains 0.5, 1 and 2, respectively, while the estimated efficacy rates for M. haemolitica were 100, 95 and 3% and according to the CIM of strains 0.5, 1 and 2, respectively. The probability of obtaining the bacteriological cure after treatment decreased in a highly significant way for infections caused by bacteria with MICs higher than 0.5 μg/ml for P. multocida (p˂0.01) and 1 μg/ml for M. haemolitica (p˂0.01). The results showed the need to incorporate bacteriological isolation, the determination of the MIC and the optimization of the therapeutic dose according to the susceptibility of P. multocida and M. haemolitica strains in the therapeutic protocol to avoid therapeutic failures and consequently promote the development of bacterial resistance.